Improving Students’ Vocabulary Mastery by Using Audio-Lingual Method on Grade VIII Students of SMP Negeri 4 Pematang Siantar - Ika Purnama Sari; Jernih Sinurat (English Lecturers and Teachers Association (ELTA), 2022)
This study is based on the important of vocabulary. Vocabulary is an important component of language use because Vocabulary is one of the aspects of language besides grammar and pronunciation. In this research, the researcher using Audio-Lingual Method to improve students’ mastery vocabulary. The main objective of this study is to describe the use of Audio-Lingual Method in teaching and to identify how much students’ mastery in vocabulary improvement after being taught by using Audio-Lingual Method. This study is classroom action research that was done in two cycles. The data collection was done using observation and test. The data from the observation that had been taken from every cycle analyzed descriptively while the data from test were analyzed quantitatively. The use of Audio - Lingual Method in teaching at class VIII - 2 Students of SMP Negeri 4 Pematangsiantar was conducted in two cycles including cycle one and cycle two. The participant of this study was 32. The result of this study shows that using Audio-Lingual Method can improve students’ mastery vocabulary. This is proven by students’ test score that improved in every cycle. In the first cycle, the students’ average score was 60,00 and in the second cycle students got 68,90 and the Post cycle 76,56. Audio-Lingual Method is an appropriate technique used to improve students’ mastery vocabulary. The result of this study is helpful information for English teachers in teaching vocabulary Key words: Improving, Mastery Vocabulary, Audio-Lingual Method, Classroom Action Research